System resilience and neighbourhood action on social determinants of health inequalities: an English Case Study. (July 2022) - Popay, J; Kaloudis, H; Heaton, L; Barr, B; Halliday, E; Holt, V; Khan, K; Porroche-Escudero, A; Ring, A; Sadler, G; Simpson, G; Ward, F; et al.
Aims: This article seeks to make the case for a new approach to understanding and nurturing resilience as a foundation for effective place-based co-produced local action on social and health inequalities. Methods: A narrative review of literature on community resilience from a public health perspective was conducted and a new concept of neighbourhood system resilience was developed. This then shaped the development of a practical programme of action research implemented in nine socio-economically disadvantaged neighbourhoods in North West England between 2014 and 2019. This Neighbourhood Resilience Programme (NRP) was evaluated using a mixed-method design comprising: (1) a longitudinal household survey, conducted in each of the Neighbourhoods For Learning (NFLs) and in nine comparator areas in two waves (2015/2016 and 2018/2019) and completed in each phase by approximately 3000 households; (2) reflexive journals kept by the academic team; and (3) semi-structured interviews on perceptions about the impacts of the programme with 41 participants in 2019. Results: A difference-in-difference analysis of household survey data showed a statistically significant increase of 7.5% (95% confidence interval (CI), 1.6 to 13.5) in the percentage of residents reporting that they felt able to influence local decision-making in the NFLs relative to the residents in comparator areas, but no effect attributable to the NRP in other evaluative measures. The analysis of participant interviews identified beneficial impacts of the NRP in five resilience domains: social connectivity, cultural coherence, local decision-making, economic activity, and the local environment. Conclusion: Our findings support the need for a shift away from interventions that seek solely to enhance the resilience of lay communities to interventions that recognise resilience as a whole systems phenomenon. Systemic approaches to resilience can provide the underpinning foundation for effective co-produced local action on social and health inequalities, but they require intensive relational work by all participating system players.